2016
DOI: 10.1186/s12971-016-0092-9
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to cigarette smoking among secondary and high school students from a socially disadvantaged rural area in Poland

Abstract: BackgroundTo prevent adolescents from becoming smokers, it is essential to understand factors that cause them to become susceptible to smoking (SS). The aim of this study was to examine association between individual and school characteristics and susceptibility to smoking initiation and experimentation in the youth.MethodsWe collected cross-sectional survey data from students aged 13–19 years attending 21 schools from Piotrkowski district. Of 4050 students, 3552 respondents, including 2508 non-smokers, filled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
46
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(65 citation statements)
references
References 34 publications
18
46
1
Order By: Relevance
“…Several studies laminated to the fact that to prevent adolescents from becoming smokers, it is necessary to know factors that cause them to become susceptible to the habit of smoking. Personal, social and environmental factors are strongly correlated smoking initiation [19]. These facts may express our findings that all social and environmental variables were found to increase the likelihood of initiating smoking.…”
Section: Discussionsupporting
confidence: 76%
“…Several studies laminated to the fact that to prevent adolescents from becoming smokers, it is necessary to know factors that cause them to become susceptible to the habit of smoking. Personal, social and environmental factors are strongly correlated smoking initiation [19]. These facts may express our findings that all social and environmental variables were found to increase the likelihood of initiating smoking.…”
Section: Discussionsupporting
confidence: 76%
“…These results have many possible interpretations. With regard to the influence of gender and age on susceptibility to smoking, many studies [38][39][40][41] have taken them into account, but the results have been mixed, with some finding a statistically significant association and others that did not. These studies' populations have different age distributions and come from different countries with very different cultural backgrounds, thus, it is difficult to draw conclusions about gender and age in general.…”
Section: Main Findings and Comparison With Other Studiesmentioning
confidence: 99%
“…As a social factor that is among the most significant determinants of adolescents' smoking (Tyas & Pederson, ), social norms, such as prevalence and approval, are associated with adolescents' smoking intention and smoking behaviors (Powell, Tauras, & Ross, ). Polańska, Wojtysiak, Bąk‐Romaniszyn, and Kaleta () reported that young people's susceptibility to smoking might differ depending on social factors, such as social and cultural norms regarding youth smoking in various countries. Furthermore, the significance of social norms regarding smoking on smoking intention might depend on cultural background (Duff, Puri, & Chow, ).…”
Section: Introductionmentioning
confidence: 99%
“…Pola nska, Wojtysiak, Bąk-Romaniszyn, and Kaleta (2016) reported that young people's susceptibility to smoking might differ depending on social factors, such as social and cultural norms regarding youth smoking in various countries. Furthermore, the significance of social norms regarding smoking on smoking intention might depend on cultural background (Duff, Puri, & Chow, 2011).…”
Section: Introductionmentioning
confidence: 99%